Primer binding sites corresponding to several tRNA species are present in DNAs of different members of the same retrovirus-like gene family (VL30). - Itin, A (1985)
We analyzed the putative tRNA primer binding site (PBS) present in several cloned copies of the murine retrovirus-like VL30 family. In the five VL30 DNA clones analyzed, we identified PBS sequences corresponding to three different tRNA species: tRNAPro, tRNAGly, and tRNAGln. The latter two PBS sequences have not been previously encountered in other retroviral or retrovirus-like systems. A unique situation was observed in which PBS sequences complementary to two different tRNA species were flanked by otherwise identical VL30 sequences. In addition, we demonstrated the use of PBS-specific synthetic oligonucleotides for the identification of the tRNA primer and their potential utility in the direct cloning of PBS-containing DNA elements.